La bala no mata - Paz Ybarnegaray, Gabriela (Universidad Mayor de San Andrés : Fundación Grupo UKAMAU, 2011)
A look at the past from the present. La Paz - Bolivia, 60 years after the Bolivian Revolution. A group of people who were on the verge of death at that time and who, by chance or destiny, already old, tell us their stories. 60 years after the National Revolution, "The bullet does not kill" reveals a group of people who survived and led the revolution. Ordinary people who lived through this fundamental event in the history of Bolivia and who are now around 70 to 90 years old. Through the stories of these people, who remained anonymous throughout this time, we can situate ourselves and imagine the main battles that made the National Revolution possible. Along with these men and women, we will visit the places from which they participated in the revolutionary struggle on April 9, 10 and 11, 1952, to relive their experiences step by step.--